MEASURES OF STATE SUPPORT OF REGIONAL PROGRAMS OF DEVELOPMENT OF AGROINDUSTRIAL COMPLEX OF THE NORTH CAUCASUS AND SOUTHERN FEDERAL DISTRICTS - lima Rykova; Roman Gubanov; Irina Maeva (Вестник Северо-Кавказского федерального университета, 2022)
The article examines the key issues of organization of budget financing of development of agriculture in general, and support regional programs of functioning of agriculture in the North Caucasus Federal District and Southern Federal District in particular. We give comments and analytical calculations of budget allocation structure implemented by the programme on agriculture. We estimate the current and future state subsidies RF subjects, depending on the extent of regional programs of development of agribusiness and agricultural sectors. Illustrating the system of state support measures of regional programs of development of agribusiness North Caucasus Federal District and Southern Federal District. The forecast of the amounts of subsidies for the provision of decoupled support to agricultural producers in the area of crop production in the period until 2019.